PARTISIPASI PEREMPUAN DALAM POLITIK DAN PEMBANGUNAN DI BANTEN - Listyaningsih Listyaningsih (Universitas Sultan Ageng Tirtayasa, 2010)
Humans as a citizen is a subject at once the object of development in Indonesia. However, at the regional level is not the case, especially in villages far from urban civilization. The presence of women has not been evident in every movement of development in Banten. Thus attracting researchers to conduct more in-depth study on women's participation in politics and development in Banten. The research was conducted using qualitative methods with a view to facilitate researchers in capturing qualitative data in the form of exploration. Results showed that women's participation in politics and development is still lagging behind by men that is caused by two factors: structural factors and cultural factors surrounding the social, cultural and political situation in Banten Province.